Analisis Penggunaan Sistem Informasi Mumtaz dalam Meningkatkan Efektivitas Administrasi Sekolah di SD Integral Luqman Al-Hakim Mataram - Baiq Diyat Radya; Hani Tazkiyah Mubarokah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was conducted because Luqman Al-Hakim Integral Elementary School has been using the in various school administrative activities, but no in-depth study has ever been conducted regarding the effectiveness of its use. However, the use of the right information system can help improve the quality of school administrative services. Therefore, this research is important to determine how the Mumtaz Information System is used and its contribution to improving the effectiveness of school administration at Integral Luqman Al-Hakim Elementary School in Mataram. This study employs a qualitative approach using the case study method. The research subjects include the school principal, school operators, teachers, parents, and students. Data collection techniques were conducted through interviews, observations, and documentation. Data analysis utilized the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Mumtaz Information System has been actively used in various school administrative activities, such as the admission of new students, payment management, student data storage, and the online dissemination of information to parents. The use of this system enhances the effectiveness of school administration by reducing data entry errors, streamlining administrative processes, and facilitating structured data access and storage. Additionally, the quality of administrative services becomes faster, more effective, efficient, accurate, and transparent. This system also offers various benefits for schools and parents, such as ease of data management, increased administrative transparency, easy access to payment information, and strengthened communication between schools and parents. Thus, the use of the Mumtaz Information System has proven capable of supporting improved school administrative effectiveness and the quality of educational services at SD Integral Luqman Al-Hakim.